2018
DOI: 10.1186/s12882-018-0968-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced podocyte apoptosis is mediated by endoplasmic reticulum stress/PKC-δ/p38 MAPK pathway activation and trough increased Na+/H+ exchanger isoform 1 activity

Abstract: BackgroundAngiotensin II (Ang II) contributes to the progression of renal diseases associated with proteinuria and glomerulosclerosis mainly by inducing podocyte apoptosis. In the present study, we investigated whether the chronic effects of Ang II via AT1 receptor (AT1R) would result in endoplasmic reticulum (ER) stress/PKC-delta/p38 MAPK stimulation, and consequently podocyte apoptosis.MethodsWistar rats were treated with Ang II (200 ng·kg−1·min−1, 42 days) and or losartan (10 mg·kg−1·day−1, 14 days). Immort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 55 publications
1
36
1
Order By: Relevance
“…Moreover, PKCd activation has also been reported to be related to therapy resistance. For instance, a study indicated that fractionated radiation induced an increase in the glioma-initiating cell population and less sensitivity to cancer treatment and reported to be phosphorylated and activated by PKCd (30,31,36,37), our data showed that only Akt but neither p38 nor JNK1/2 was involved in tumor repopulation in a PKCd-dependent way. Further studies will be needed to understand the preferential use of Akt as the downstream effector of PKCd over the other two.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, PKCd activation has also been reported to be related to therapy resistance. For instance, a study indicated that fractionated radiation induced an increase in the glioma-initiating cell population and less sensitivity to cancer treatment and reported to be phosphorylated and activated by PKCd (30,31,36,37), our data showed that only Akt but neither p38 nor JNK1/2 was involved in tumor repopulation in a PKCd-dependent way. Further studies will be needed to understand the preferential use of Akt as the downstream effector of PKCd over the other two.…”
Section: Discussionmentioning
confidence: 57%
“…The activation of PKCd after ionizing radiation has been shown to affect the function of several signal transduction proteins. Akt, p38 kinase, and c-Jun N-terminal kinase/stress-activated protein kinase (JNK/SAPK or JNK1/2) were shown to act downstream of protein kinases and be involved in regulating the cell cycle, cell proliferation, cell survival, and carcinogenesis (30)(31)(32)(33)(34)(35)(36)(37)(38). Therefore, we decided to investigate the activities of those proteins in irradiated dying cells to see if they were involved in tumor repopulation during radiotherapy.…”
Section: Akt Is Activated By the Caspase-3/pkcd Signaling In Dying Tumentioning
confidence: 99%
“…Recent studies have shown that Ang II can activate and/or trigger various cellular events (e.g. oxidative stress and reactive oxygen species overproduction, endoplasmic reticulum stress, autophagy and mitochondrial dysfunction), thus resulting in cytoskeletal rearrangement and podocyte apoptosis [4][5][6][7][8][9]. Notably, NADPH oxidase (Nox) plays a critical role in driving reactive oxygen species (ROS) production.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the effects of angiotensin II on the lung interstitium can promote apoptosis, which, in turn, initiates an inflammatory process with release of proinflammatory cytokines, establishing a self‐powered cascade (Cardoso et al, 2018). In certain patients, this process reaches such clinical relevance that requires external oxygen supply and in severe cases an Acute Respiratory Distress Syndrome (ARDS) ensues (this correlates with an acute release ‐storm‐ of cytokines) (Ware & Matthay, 2000).…”
mentioning
confidence: 99%